Treatment of hypertension during pregnancy - Hall, David (SA Heart Journal, 2017)
Hypertensive disorders of pregnancy are on the increase and remain important causes of maternal and perinatal morbidity and mortality. The different classes of hypertension carry different risks but severe hypertension in itself remains a medical emergency. Pre-eclampsia is a particularly dangerous condition that may progress rapidly. During pregnancy mild hypertension without end-organ disease does not require treatment until levels of 150/100mmHg are reached. Acute severe hypertension must be diagnosed and treated expeditiously. The choice of anti-hypertensive agents is limited in pregnancy and physicians should choose agents which are regarded as safe and which they feel comfortable in using. After acute management, oral maintenance therapy will be indicated in many cases, although delivery is regarded as the only defi nitive treatment for pregnancy specifi c conditions such as pre-eclampsia. Previous pre-eclampsia is associated with increased rates of cardiovascular and metabolic disease in later life. This should prompt subsequent lifestyle education and intervention.